Konseling Individual dengan Teknik Kontrak Perilaku untuk Mengatasi Prokrastinasi Akademik Mahasiswa - Uhwah Hasanah (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
This study aimed to overcome Academic Procrastination behavior which faced by the students in Math department by giving them individual counseling using behavior contract technique. Academic Procrastination was a behavior of consciously and repeatedly delaying a task. This study used qualitative method with descriptive design. The subjects of this study were two students. In data collection, the researcher conducted observation, interview and open ended question for four meetings. Reseracher as a counsellor gave an instrument before and after giving the counseling services. The result of this study was the students able to overcome academic procrastination. This case was proved from monitoring result that counseling activities for two weeks made the students able to finish the task without delaying it and they could submit the task based on due date. The case also can be seen from the result of instrument which given before and after the individual counseling services using behavior technique that showed the significant change namely all the tasks have been finished.